Implantation - Aplin, John (Henry Stewart Talks, 2019)
Preimplantation development, Preparation of the human endometrium for implantation, The development of the blastocyst, Hormone interactions and their association with embryo attachment and implantation, The implantation window in humans, Embryo selectivity in humans, Embryo attachment to the endometrium, Decidualisation of endometrial stroma, Early pregnancy nutrition